2013
DOI: 10.1063/1.4856395
|View full text |Cite
|
Sign up to set email alerts
|

Effect of substrate temperature on the magnetic properties of epitaxial sputter-grown Co/Pt

Abstract: Epitaxial Co/Pt films have been deposited by dc-magnetron sputtering onto heated C-plane sapphire substrates. X-ray diffraction, the residual resistivity and transmission electron microscopy indicate that the Co/Pt films are highly ordered on the atomic scale. The coercive field and the perpendicular magnetic anisotropy increase as the substrate temperature is increased from 100-250C during deposition of the Co/Pt. Measurement of the domain wall creep velocity as a function of applied magnetic field yields th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 26 publications
(30 reference statements)
2
20
0
Order By: Relevance
“…We studied Pt(3 nm)/Co(0.8 nm)/Pt 1−x Au x (3 nm) trilayers with x = 0, 0.5, and 1 that were prepared by sputtering at high temperatures, as described previously [38,39]. The main points of the growth method are that a seed Pt layer was sputtered onto a C-plane sapphire substrate at 500 • C, followed by Co at a substrate temperature of 100 • C. The Pt 1−x Au x layer was grown by co-sputtering from Pt and Au targets at 100 • C, with the sputtering powers adjusted to keep the rate ∼ 1Å/s.…”
Section: Epitaxial Trilayer Growth and Characterizationmentioning
confidence: 99%
“…We studied Pt(3 nm)/Co(0.8 nm)/Pt 1−x Au x (3 nm) trilayers with x = 0, 0.5, and 1 that were prepared by sputtering at high temperatures, as described previously [38,39]. The main points of the growth method are that a seed Pt layer was sputtered onto a C-plane sapphire substrate at 500 • C, followed by Co at a substrate temperature of 100 • C. The Pt 1−x Au x layer was grown by co-sputtering from Pt and Au targets at 100 • C, with the sputtering powers adjusted to keep the rate ∼ 1Å/s.…”
Section: Epitaxial Trilayer Growth and Characterizationmentioning
confidence: 99%
“…To avoid such ambiguities and in order to explore this systematically one has to grow such materials in a controlled way. Here we experimentally investigate epitaxial layers of Pt/Co/Au x Pt 1−x prepared by sputtering onto single crystal sapphire substrates 18 . Pt is a common pairing with Co that has strong PMA and DMI 16 , and is close to satisfying the Stoner criterion 19 , giving strong proximity magnetism.…”
Section: Introductionmentioning
confidence: 99%
“…• C, where a high degree of crystallographic ordering was found previously [28]. Films were grown with the base pressure in the range 1.1 × 10 −7 to 3.3 × 10 −7 Torr, measured immediately prior to deposition of the seed layer.…”
Section: Sample Depositionmentioning
confidence: 99%
“…• C for optimum smoothness [28]. Measurements of the residual resistivity ratio (RRR) and the full width at half maximum (FWHM) of the x-ray diffraction rocking curves in previous work [28] showed that sputtering onto a C-plane sapphire substrate held at a temperature between 450…”
Section: Sample Depositionmentioning
confidence: 99%